The return of raptors to Scotland's skies: Investigating the diets of reintroduced red kites and white-tailed eagles using stable isotopes. - Juliette Waterman; Stuart Black; Naomi Sykes; Andrew C Kitchener; William F Mills; Mark D E Fellowes (PLoS ONE)
Species reintroductions are increasingly seen as important methods of biodiversity restoration. Reintroductions of red kites Milvus milvus and white-tailed eagles Halieaeetus albicilla to Britain, which were extirpated in the late 19th and early 20th centuries, represent major conservation successes. Here, we measured stable isotope ratios of carbon (δ13C) and nitrogen (δ15N) in feather keratin and bone collagen of museum specimens of red kites and white-tailed eagles, which were collected from across Scotland between the 1800s and 2010s. Our objectives were to investigate dietary differences between species and between the pre- and post- reintroduction periods. Among reintroduced birds, δ13C values were significantly less negative and δ15N values higher in feather keratin and bone collagen of white-tailed eagles compared to red kites, likely reflecting a greater reliance on marine resources by the former. Our stable isotope data showed a wide range, confirming the dietary diversity observed in conventional diet studies of both taxa, with white-tailed eagles, in particular, having wide dietary niches and a considerable degree of inter-individual variability. Isotopic data from pre-introduction red kites mostly fell within the range of post-reintroduction birds, suggesting they had similar diets to the pre-reintroduction birds, or the prey base for modern birds is isotopically indistinguishable from that of their historic counterparts. For white-tailed eagles, several pre-reintroduction birds were isotopically distinct from the post-reintroduction population. These differences may indicate a changing prey base, although these conclusions are complicated by shifting distributions and small population samples. Overall, our study demonstrates the utility of natural history collections in examining changes in diet, environment, and interactions with humans in reintroduced species compared with pre-extirpation indigenous populations.